p63 Directs Subtype-Specific Gene Expression in HPV+ Head and Neck Squamous Cell Carcinoma - Glathar, Alexandra Ruth; Oyelakin, Akinsola; Gluck, Christian; Bard, Jonathan; Sinha, Satrajit (Frontiers in Oncology, 2022)
The complex heterogeneity of head and neck squamous cell carcinoma (HNSCC) reflects a diverse underlying etiology. This heterogeneity is also apparent within HPV+ HNSCC subtypes, which have distinct gene expression profiles and patient outcomes. One aggressive HPV+ HNSCC subtype is characterized by elevated expression of genes involved in keratinization, a process regulated by the oncogenic transcription factor dNp63. Furthermore, HPV oncoproteins drive dNp63 expression, suggesting an unexplored functional link between dNp63 and HPV+ HNSCC. Here we show that HPV+ HNSCCs can be molecularly stratified according to dNp63 expression levels and derive a dNp63-associated gene signature profile for such tumors. We leveraged RNA-seq data from p63 knockdown cells and ChIP-seq data for p63 and histone marks from two dNp63high HPV+ HNSCC cell lines to identify an epigenetically refined dNp63 cistrome. Our integrated analyses reveal crucial dNp63-bound super-enhancers likely to mediate HPV+ HNSCC subtype-specific gene expression that is anchored, in part, by the PI3K-mTOR pathway. These findings implicate dNp63 as a key regulator of essential oncogenic pathways in a subtype of HPV+ HNSCC that can be exploited as a biomarker for patient stratification and treatment choices.